THE DIMENSION OF SUFISM IN THE VERSES OF HAJJ: AN ANALYSIS OF THE ESOTERIC MEANING OF HAJJ FROM THE PERSPECTIVE OF LAṬĀ’IF AL-ISHĀRĀT - Eko Suryaddin Zain; Muhammad Zulfikar Nur Falah (Sekolah Tinggi Agama Islam Sadra, 2026)
This study examines the mystical dimensions of the verses concerning the rites of the Hajj from the perspective of Abū al-Qāsim al-Qushayrī in Laṭā’if al-Ishārāt. The issue is that, in the public perception, the Hajj tends to be viewed merely as a ritual of Islamic law. Conversely, the Hajj also possesses a fundamental dimension as a form of spiritual journey. This comprehensiveness underpins the urgency of the Hajj, which is so compatible with Sufi discourse. Previous research on the material aspects of the Hajj has been limited to a descriptive review of the interpretative meanings of the Qur’an alone. Therefore, the esoteric meanings of the rituals from al-Qushayrī’s perspective form the focus of this study to examine the spiritual journey’s dimension within the Hajj, thereby ensuring objectivity is evident in the completeness of the elements of the worship process. This study employs library research utilizing the method of Sufi exegesis analysis. Primary data is drawn from Laṭā’if al-Ishārāt, whilst secondary data encompasses Sufi exegetical literature and studies on Sufism. Analysis is conducted through an examination of the verses concerning the rituals of the Hajj and an exploration of the inner meanings contained within them. The research findings indicate that each Hajj ritual possesses an esoteric structure of meaning: iḥrām is understood as the emptying of the ego (takhallī) and the strengthening of the etiquette of presence (taḥallī), wuqūf and mabīt at Muzdalifah as a means of self-annihilation (fanā’), the stoning of the jamrah and mabīt at Mina as the pinnacle of divine witnessing (mushāhadah and ma‘rifah), whilst ṭawāf and sa‘ī represent the manifestation of divine revelation (tajallī) leading to the final stage of becoming a perfect human being (insān kāmil). Al-Qushayrī’s interpretation affirms that the sequence of rituals constitutes a process of spiritual transformation towards the perfect human being. The implication is that this finding enriches the study of Sufi exegesis whilst making a practical contribution to the development of Hajj rituals by emphasizing the integration of Sharia and spiritual depth.